Business telephoning in praetice - Richards, David (Language Key Ltd, 1994)
Sách do giáo viên cung cấp; When we have to use English as a second language to communicate, we can easily be at a disadvantage in our conversations with native speakers. If we are aware of that disadvantage we may lack confidence and so provide the people we are conversing with an opportunity to control dialogue in a way that stops us from achieving the outcome we need.; AV291